Fashion writing : a primer - Claudia B Manley; Slone, Abi (London Routledge Taylor and Francis Group, 2023)
Acting as a comprehensive primer for the field of fashion writing, this book provides an accessible entry point for readers from diverse backgrounds, giving them a clear understanding of the intricacies of fashion writing, the outlets in which it appears, and the possibilities beyond the page.
Keywords: Writing about the arts and leisure